Dirac system with a singularity in an interior point. Issue 11 (1st November 2016) - Gorbunov, Oleg; Shieh, Chung-Tsun; Yurko, Vjacheslav
Abstract : We study the non-selfadjoint Dirac system on the line having an non-integrable regular singularity in an interior point with additional matching conditions at the singular point. Special fundamental systems of solutions are constructed with prescribed analytic and asymptotic properties. Behavior of the corresponding Stokes multipliers is established. These fundamental systems of solutions will be used for studying direct and inverse problems of spectral analysis.